A METADISCOURSE ANALYSIS OF RESEARCH ARTICLE ABSTRACTS ACROSS ENGLISH, INDONESIAN, AND ARABIC AUTHORED BY INDONESIAN ISLAMIC HIGHER EDUCATION SCHOLARS - Yudhiantara, Rully Agung; Kurniawan, Eri; Al Farisi, Mohamad Zaka (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
This study examines the use of metadiscourse in English, Indonesian, and Arabic research article abstracts from the Studia Islamika journal, published between 2014 and 2023. Focusing on enhancing cross-cultural academic communication, the research analyzes how authors affiliated with Islamic higher education institutions employ metadiscourse to engage readers and position their work within the scholarly field. Using Hyland's (2005) metadiscourse framework, the study identifies distinct patterns in the distribution and realization of interactive and interactional metadiscourse elements across the three languages. Transitions are the most frequently employed interactive feature, with a stronger reliance on frame markers in Indonesian and Arabic abstracts. However, the absence of self-mentions and engagement markers across all three languages suggests a shared preference for a formal academic tone. These findings provide valuable insights into metadiscourse practices in Islamic studies abstracts, offering guidance for scholars in preparing manuscripts for publication. Additionally, this research underscores the importance of focusing on metadiscourse in academic writing within language education departments at Islamic higher education institutions, enhancing scholars’ writing skills and promoting awareness of cultural and linguistic nuances when addressing a global audience.